Selective effects of the APOE epsilon4 allele on presynaptic cholinergic markers in the neocortex of Alzheimer's disease. - Lai, M; Tsang, S; Garcia-Alloza, M; Minger, S; Nicoll, J; Esiri, M; Wong, P; Chen, C; Ramírez, M; Francis, P (2006)
The effects of the APOE epsilon4 allele on a range of pre- and postsynaptic cholinergic markers were studied in a cohort of community-based Alzheimer's disease (AD) patients. Compared with age-matched controls, the postmortem AD neocortex showed decreased choline acetyltransferase (ChAT) and acetyl cholinesterase activities, lower muscarinic M2, and nicotinic alpha4beta2 receptor densities, as well as reduced M1 receptor coupling to G-proteins. However, the epsilon4 allele was dose-dependently correlated only with higher losses of ChAT activities. AD patients with two epsilon4 alleles also had more beta-amyloid containing senile plaques in the temporal cortex compared to patients with 0/1 epsilon4. This study suggests that APOE epsilon4 selectively affects presynaptic cholinergic function which may contribute to the clinical and neuropathological features of AD.